Penggunaan Media Massa dan Media Sosial di Kalangan Mahasiswa Komunikasi - Azman (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
Mass media is considered the fourth pillar in the enforcement of democracy in a country. Freedom in the delivery of information is desirable, as well as the information which is very responsible responsible for the dissemination of such information. Since the presence of new media, in various forms, especially social media greatly impact on users. However, the use and dissemination of information through media that can be freely biased is not yet biased to provide a high trust and even hoax information. This paper was written to examine the use of mass media and social media among students of communication in obtaining various information. Most of the communication students are more confident in mass media in getting information because the information reviewed in mass media is more accurate. But in the use of social media is used to build a more intimate relationship, and make social medias like whatsapp as lecture discussion group, school alumni group, organization group, business building group and others. But the tendency of communication students today more information through social media than the mass media. And even more often they read the information through social media rather than the mass media that is already rare for them.